1998
DOI: 10.1002/jmri.1880080418
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of arterial pulse‐wave velocity measurement using MR

Abstract: The performance of a one-dimensional MR technique for the estimation of pulse-wave velocity in the aorta was evaluated. An expression for the error in this estimate was formulated and verified both by simulation and by experiment. On the basis of this formulation, guidelines for increasing the efficiency of the acquisition were established. The technique was further validated by comparison with pulse-wave velocity measurements made with a pressure catheter. All data were acquired from a latex tube driven by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
72
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 25 publications
(44 reference statements)
0
72
0
Order By: Relevance
“…The aortic propagation pulse-wave was estimated from the ratio of the distance between two sections of the thoracic aorta (ascending and descending) over the time lag between the mean velocity curves vs. time obtained at these sections (12). This time lag (⌬t) was defined as the difference between two linear fittings of the velocity rise at the intersection of the time axis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aortic propagation pulse-wave was estimated from the ratio of the distance between two sections of the thoracic aorta (ascending and descending) over the time lag between the mean velocity curves vs. time obtained at these sections (12). This time lag (⌬t) was defined as the difference between two linear fittings of the velocity rise at the intersection of the time axis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MRI methods of measuring blood flow velocity (7), total acceleration (8), pressure mapping (9 -11), and vessel compliance (12) have been well validated. Unlike other methods of measuring fluid motion, such as Doppler, MRI provides measurements of total acceleration (8), and indices for post-load (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For PWV estimation, typically transit-time methods are employed estimating temporal differences of specific features of blood flow waveforms, e.g., time from foot to foot or peak to peak, between two locations of the vessel with known distance (11-24). However, the precision of this method highly depends on the exact calculation of flow difference and distance between only two measuring points (16,25,26).Methodological improvements include a more continuous evaluation along a vessel center line and cross-correlation (XCor) analysis for the estimation of waveform delays, which improved the accuracy of PWV estimation but relied on 2D PC acquisitions in sagittal oblique slices exactly transecting the thoracic aorta (27,28). Recently, more comprehensive three-dimensional (3D) CINE techniques in combination with three-directionally encoded velocities (flow-sensitive four-dimensional [4D] MRI) have been reported that provide information on multidirectional in vivo blood flow with full volumetric coverage of the vessel of interest (29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…For PWV estimation, typically transit-time methods are employed estimating temporal differences of specific features of blood flow waveforms, e.g., time from foot to foot or peak to peak, between two locations of the vessel with known distance (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). However, the precision of this method highly depends on the exact calculation of flow difference and distance between only two measuring points (16,25,26).…”
mentioning
confidence: 99%